FEAR OF COMMITMENT AMONG COLLEGE STUDENTS: ADAPTATION AND TESTING OF THE INSTRUMENT’S VALIDITY AND RELIABILITY - Sukma Ayu Putri Titah Dewi; Henny Indreswari; Khairul Bariyyah (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Fear of commitment is a psychological phenomenon related to individuals difficulty in forming commitment in romantic relationships. During emerging adulthood, particularly among university students, individuals begin to face social expectations to develop more serious relationships and consider long term commitment. This condition makes the measurement of fear of commitment important using instruments with adequate psychometric quality. This study aims to adapt and examine the validity and reliability of a fear of commitment instrument for university students. The study employed a quantitative approach with an instrument development design. The participants consisted of 221 students from Universitas Negeri Malang, including undergraduate, master, and doctoral students. The instrument consisted of 17 items using a four point Likert scale. Data analysis was conducted using JASP software through item total correlation to test validity and Cronbach Alpha coefficient to test reliability. The results showed that seven items met the validity criteria, namely item 1, item 4, item 7, item 9, item 10, item 12, and item 13. Reliability testing of these seven items produced a Cronbach Alpha value of 0.590 indicating moderate internal consistency. The findings indicate that the fear of commitment instrument has potential to be used as an initial measurement tool in studies related to romantic relationship commitment dynamics among university students.